The Triptych of Dorian Gray (1890–91): Reading Wilde’s Novel as Three Print Objects - Brett Beasley (Cahiers Victoriens et Edouardiens)
Oscar Wilde’s novel The Picture of Dorian Gray has the rare distinction of having not only controversial content, but a controversial textual history as well. In fact, the two are inseparable. The prosecutors in Wilde’s trials made use of the fact that Wilde had changed—or ‘purged’, as they put it—many aspects of the novel after its first appearance in Lippincott’s Monthly Magazine. But neither they nor the majority of Wilde readers knew that his original typescript had already undergone a great deal of censorship without Wilde’s permission before the novel found its way into print. In this paper I investigate these three texts—the typescript, the magazine version, and the first edition—using both the methods of textual studies and the methods of social and literary history, showing that the various texts of The Picture of Dorian Gray actually embody different arguments about the status of material objects themselves. Wilde’s only novel has long been recognized as a critique of Victorian society, but only by understanding it as social in its material instantiations can we come to understand the full scale and shape of that critique today.